Velocidade de infiltração da água em um latossolo amarelo submetido a diferentes sistemas de manejo - Cunha, Jorge Luiz Xavier Lins (2008)
Water and soil are key factors in the definition of the appropriate exploration of an agricultural area. Infiltration is a dynamic process by means of which water enters the soil, both in the descending vertical as well as in horizontal direction. The knowledge of the infiltration rate in the soil is of paramount importance in order to define the conservation, planning and dimentioning of irrigation and drainage systems. Aiming at estimating the infiltration rate in a hard dystrophic yellow Latossoil in a coastal plateau area in the State of Alagoas, an experiment was carried out consisting of three different soil preparations: conventional, minimal cultivation and direct planting, in which infiltration tests were carried out in order to compare the different empirical equations models by Kostiakov, Kostiakov-Lewis and Horton. The soil had been explored with corn cultivation (Zea Mays) for several years and in 2007 soya was cultivated there. For infiltration speed rate determination, ring infiltrometer technique was adopted. When the infiltration rate obtained in the field and the different empirical models were compared, it was possible to observe that the Kostiakov model presented the best correlation being statiscally different at the 1% probability level compared to the other models, whereas the minimal cultivation presented the best infiltration rate when compared to the conventional and direct plantings, differing statically (p ≤ 0,01).